Judicial Reasoning on Force Majeure in Banking Credit Agreements Following Natural Disasters - Moh. Nur Rahmat Cono; Nirwan Junus; Mohamad Taufiq Zulfikar Sarson (Yayasan Cerdas Pedia Indonesia, 2026)
This article examines judicial reasoning in determining whether a debtor’s failure to perform obligations under a banking credit agreement following a natural disaster constitutes force majeure or breach of contract. It applies normative legal research using statutory, conceptual, and case approaches, with a comparative analysis of Decision Number 9/Pdt.G/2019/PTA.Gtlo of the Gorontalo Religious High Court and Decision Number 97/Pdt.G/2020/PA.Pal of the Palu Religious Court. The study finds that the Gorontalo decision recognized relative overmacht and restricted collateral execution, whereas the Palu decision rejected force majeure because the contractual object remained usable and the debtor lacked sufficient good faith. These differing approaches create uncertainty for creditors in debt recovery, restructuring, and collateral execution. The article proposes assessment indicators based on causation, the condition of the collateral, the temporary or permanent nature of the impediment, debtor good faith, restructuring efforts, and proportional creditor action.